Analysis of trace elements, cholinesterase inhibitory activity, and adme/tox profiling of some achillea species - (:unkn) unknown (Turkish Chemical Society, 2021)
In this study, the anti-cholinesterase activities of different extracts of Achillea lycaonica, A. vermicularis and A. nobilis L. subsp. neilreichii (Kerner) Formanek species were examined and then trace elements (Al, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Cd, and Pb) of the plants were analyzed by ICP-MS. The pharmacokinetic properties of the phenolic compounds of these plants previously analyzed by us and the ADME-Tox (absorption, distribution, metabolism, excretion, and toxicity) profiles of the trace elements we identified in this study were estimated. According to the data obtained, it was determined that all three plants showed high acetyl-cholinesterase inhibitory activity. The concentration of trace elements was lower than that declared by WHO, except for the A. lycaonica. It was determined that V, Cr, Fe, Co, and As metals in A. lycaonica exceeded the limit values determined by WHO. According to ADMET estimates, it is thought that the toxic values of all three plants are not high, and therefore the use of A. nobilis and A. vermicularis plants does not pose any health risk but A lycaonica should be used carefully due to the presence of heavy metals. © 2021, Turkish Chemical Society. All rights reserved.
Keywords: ADMET; Cholinesterase inhibitory; ICP-MS; Phenolic compounds